PENGARUH STRUKTUR KEPEMILIKAN SAHAM, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DU BURSA EFEK INDONESIA - Marsinah Marsinah (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2021)
The aim of this research is to determine the influence of leadership and communication on work productivity of employees of AKPER KESDAM II/Sriwijaya Palembang. The samples used in this study were 39 employees. Data collection techniques were carried out by distributing questionnaires to employees of AKPER KESDAM II/Sriwijaya Palembang. This discussion provides information that leadership (X1) and communication (X2) simultaneously affect work productivity (Y). real or significant to the work productivity of employees of AKPER KESDAM II/Sriwijaya Palembang. From the multiple linear regression equation, we get Y=20.931+ 0.456 + 0.333 X2 + e, which means work productivity (Y) is influenced by leadership (X1) and communication (X2). The coefficient of determination (R2) between leadership (X1) and communication (X2) on work productivity (Y) Adjusted R square = 0.545 means that 54.5% of work productivity variables (Y) are influenced by leadership (X1) and communication (X2) and the remaining 45.5% is influenced by other variables